Giant River Prawns Enterprise / Muhammad Ammar Roslan ...[et al.] - Roslan, Muhammad Ammar; Noor Azmee, Nurul Syamhana; Mohd Taib, Nurfatin Inani; Norazmi, Jannatul Izzati; Rahim, Nurizatti (2014)
In a nutshell, the demand of giant river prawns is very high on the market due to its nutritional values and goodness. Due to this, Giant River Prawns Enterprise is trying to grab the opportunity to conquer the market to supply this prawns to the entire country.